2020
DOI: 10.1021/acs.analchem.0c01586
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of 13C- and 18O-Isotopes of Human Breath CO2 Using a Mid-Infrared Hollow Waveguide Gas Sensor

Abstract: Real-time measuring CO 2 isotopes ( 13 CO 2 , 12 CO 2 , and 18 OC 16 O) in exhaled breath using a mid-infrared hollow waveguide (HWG) gas sensor incorporating a 2.73 μm DFB laser was proposed and demonstrated first time based on calibrationfree wavelength modulation spectroscopy (CF-WMS). The measurement precisions for δ 13 C and δ 18 O were respectively 0.26‰ and 0.57‰ for an integration time of 131 s by Allan variance analysis. These measurement precisions achieved in the present work were at least 3.5 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Several gas sensors based on optical waveguides were designed and proposed, see e.g., [23,24]. In addition, some recent mid-IR waveguides based on CO 2 sensing have been proposed and demonstrated [25][26][27]. In comparison to conventional dielectric waveguides, plasmonic waveguides typically can be expected to feature smaller propagation lengths (i.e., intrinsic damping), which are related to the intrinsic losses within the used metals.…”
Section: Introductionmentioning
confidence: 99%
“…Several gas sensors based on optical waveguides were designed and proposed, see e.g., [23,24]. In addition, some recent mid-IR waveguides based on CO 2 sensing have been proposed and demonstrated [25][26][27]. In comparison to conventional dielectric waveguides, plasmonic waveguides typically can be expected to feature smaller propagation lengths (i.e., intrinsic damping), which are related to the intrinsic losses within the used metals.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to demonstrate the potential for disease diagnosis, similar precisions were obtained in realtime breath measurement. Compared with the gas sensor in recent work [24] mentioned in the introduction section, our system reaches a more than five times better precision on δ 13 C and δ 18 O measurements. The obtained results highlight the viability of the laser spectroscopic system in general and its potential for practical application in breath analysis.…”
Section: Discussionmentioning
confidence: 86%
“…These measurements at near infrared require the assistance of a high-finesse optical cavity or a multipath cell, which is usually accompanied by a larger volume of gas demand, so they are not really friendly for real-time online breath analysis, where the sample gas is usually limited. A hollow waveguide with a small volume was used by Zhou et al to achieve simultaneous measurement of δ 13 C and δ 18 O, and the minimum precisions were 0.26‰ and 0.57‰ for δ 13 C and δ 18 O, respectively, achieved by calibration-free wavelength modulation spectroscopy [24,25]. However, there is currently no measurement of δ 17 O in exhaled CO 2 , although studies have shown that 17 O isotopes in respiration can be used as a biomarker of brain oxygen metabolism [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Figure S12: time-resolved photo response under blue (450 nm), green (532 nm), and red (650 nm) light of 1 mW/cm 2 . Figure S13: temporal photocurrent response under blue light of various power densities (1,3,5,10,20, and 40 mW/cm 2 ). Figure S14: fitting curve of photocurrent and power density under blue light illumination.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…For example, Il-Doo Kim group fabricated colorimetric dye-loaded nanofiber yarn which is sensitive to ppm-level H 2 S and NH 3 biomarkers [15]. Zhou et al utilized a mid-infrared hollow waveguide gas sensor to realize real-time measuring of CO 2 isotopes [20]. Chen et al developed a breath analysis approach based on SERS sensor to detect fourteen volatile organic compound (VOC) biomarkers [16].…”
Section: Introductionmentioning
confidence: 99%